2021
DOI: 10.1001/jamanetworkopen.2021.11582
|View full text |Cite
|
Sign up to set email alerts
|

Home-Based vs Supervised Inpatient and/or Outpatient Rehabilitation Following Knee Meniscectomy

Abstract: Key Points Question Is inpatient and/or outpatient rehabilitation associated with better recovery compared with home-based rehabilitation after arthroscopic isolated meniscectomy? Findings This systematic review and meta-analysis compared home-based rehabilitation vs inpatient and/or outpatient rehabilitation after arthroscopic isolated meniscectomy, including 8 randomized clinical trials with a total of 434 participants. Inpatient and/or outpatient rehabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
(144 reference statements)
1
0
0
Order By: Relevance
“…When home-based exercise versus home-based exercise supplemented center-based rehabilitation, several studies ( 43 , 44 ) showed that additional center-based sessions probably showed a little increased effect. This is congruent with the findings of two reviews ( 48 , 49 ) in orthopedic rehabilitation, where they found that additional outpatient interventions were not superior to home-based rehabilitation.…”
Section: Discussionsupporting
confidence: 88%
“…When home-based exercise versus home-based exercise supplemented center-based rehabilitation, several studies ( 43 , 44 ) showed that additional center-based sessions probably showed a little increased effect. This is congruent with the findings of two reviews ( 48 , 49 ) in orthopedic rehabilitation, where they found that additional outpatient interventions were not superior to home-based rehabilitation.…”
Section: Discussionsupporting
confidence: 88%